High-Risk Neuroblastoma with Metastases to Bilateral Kidneys at Diagnosis. (30th March 2017) - Yoshikawa, Toshihide; Tanizawa, Akihiko; Suzuki, Koji; Ikeda, Kazumi; Nomura, Eishi; Maeda, Yumekichi; Tanaka, Nanae; Yamada, Kenta; Sakai, Yasuhiro; Imamura, Yoshiaki; Ohshima, Yusei
Abstract : Renal metastasis at diagnosis with neuroblastoma is rare. We present a 14-month-old boy who was diagnosed with high-risk neuroblastoma with multiple metastases, including bilateral kidneys. He received five cycles of induction chemotherapy and high-dose chemotherapy with autologous peripheral blood stem cell transplantation. All of the lesions shrank, and magnetic resonance imaging indicated that some of the metastases had disappeared. However, there were residual masses in the bilateral kidneys, and histological examination revealed the presence of tumor cells. Therefore, the patient underwent unrelated cord blood stem cell transplantation, which involved killer-ligand incompatibility in the graft-versus-host direction, in addition to human leukocyte antigen C and DRB1 mismatches. Three months later, tumor progression occurred from the residual mass in the sacral canal and a new lesion in the pancreas. Although tumor progression could not be controlled by additional chemotherapy and local radiotherapy, the metastatic nodules in bilateral kidneys did not increase in size before his death. To the best of our knowledge, this is the first report of neuroblastoma with bilateral renal metastases in the English medical literature. In addition, this case suggests that the combination of chemotherapy and immunotherapy may inhibit the progression of the renal lesions under certain conditions.